Livelihood disruption and psychological distress following the 2024 flash flood in Bangladesh - Md Mostafizur Rahman; Samantha Alam; Ifta Alam Shobuj; Md. Mehedi Hasan Santo; Md. Tanvir Hossain; Farzana Rahman; Edris Alam; Md Kamrul Islam (Scientific Reports)
Abstract The 2024 flash flood in Feni District, Bangladesh, caused substantial disruptions to livelihoods and posed serious mental health challenges for the affected population. This study aimed to assess the impact of the flood on both livelihood and psychological well-being using a cross-sectional design. Data were collected from 855 adult residents across three severely affected upazilas-Sonagazi, Chhagalnaiya, and Fulgazi. Livelihood impact was measured using a self-reported binary item, while psychological distress was assessed using the Kessler Psychological Distress Scale (K10). Descriptive and multiple regression analyses were conducted to identify key sociodemographic and flood-related predictors. Findings revealed that 99.3% of respondents experienced livelihood disruption, and over 85% reported moderate to severe psychological distress. Regression results indicated that education level, occupation, income, location, and chronic illness significantly influenced livelihood outcomes. Similarly, factors such as age, marital status, education, geographic location, family structure, and lack of early warning were significantly associated with psychological distress. Notably, limited access to safe drinking water and food scarcity during the flood exacerbated both livelihood and mental health impacts. These findings underscore the urgent need for integrated post-disaster interventions that address both economic recovery and mental health support. Enhancing early warning systems, improving resource accessibility, and strengthening community-based mental health services are critical to building resilience in flood-prone areas.